PERADABAN ISLAM DI NUSANTARA ERA WALISONGO DAN KARAKTERISTIK POLITIKNYA - Tasya Nzwa Umrotul Khasanah; Risa Majidah (CV. BAROKAH PUBLISHER, 2026)
The Wali Songo era marked a pivotal phase in the Islamization and civilization-building of Nusantara, blending spiritual propagation with strategic political engagement amid the declining Majapahit kingdom. This research examines core issues such as the cultural adaptation of Islam through local arts, architecture (e.g., Demak Mosque), and syncretic practices, alongside the political characteristics including non-violent power transitions, alliances with local rulers, and establishment of the Demak Sultanate as Islam's first political stronghold. The objective is to analyze how the Nine Saints fostered Islamic civilization while navigating political dynamics like indirect influence via royal courts and moral authority rather than conquest. Employing a historical-philosophical approach with qualitative analysis of primary sources (chronicles like Babad Tanah Jawi) and secondary literature, the study reveals key findings: the Wali Songo's tolerant, adaptive politics—characterized by cultural diplomacy, heir cultivation (e.g., Sunan Gunung Jati's statecraft), and Ahlus Sunnah wal Jamaah doctrine—ensured Islam's enduring dominance, transforming Nusantara into a hub of Islamic pluralism by the 16th century.